Role of Family Involvement and Communication Skills in Predicting Social Integration in Children with Autism - Neumann, Tobias; Meier, Johanna (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to examine the predictive roles of family involvement and communication skills in determining the level of social integration among children with autism. The research utilized a correlational descriptive design with a sample of 440 parents of children with autism residing in Germany. Participants were selected based on the Morgan and Krejcie sample size table and met inclusion criteria involving parental caregiving roles and formal autism diagnosis of their children aged 6 to 12. Data were collected using three standardized instruments: the Social Skills Improvement System Rating Scales (SSIS-RS) to measure social integration, the Family Involvement Questionnaire (FIQ) for family engagement, and the Children’s Communication Checklist–Second Edition (CCC-2) to assess communication skills. All tools have confirmed validity and reliability in previous studies. Data analysis was performed using SPSS-27, employing Pearson correlation to examine relationships among variables and linear regression to identify predictors of social integration. Descriptive statistics indicated moderate to high mean scores across all variables. Pearson correlation analysis revealed significant positive relationships between social integration and both family involvement (r = .56, p < .001) and communication skills (r = .61, p < .001). Regression analysis demonstrated that both predictors significantly contributed to the variance in social integration (R² = .45, F(2, 437) = 177.26, p < .001). Multivariate regression results confirmed that communication skills (β = .42, p < .001) and family involvement (β = .38, p < .001) were both strong, independent predictors of social integration. The findings highlight the importance of family engagement and communication development in promoting social integration among children with autism. Interventions targeting these areas may enhance social functioning and improve long-term developmental outcomes for this population.